Influence of tetracycline in the hepatic and renal development of rat's offspring - Machado, Ana Lourdes da Silva [UNESP]; Brandão, Adriana Aigotti Haberbeck [UNESP]; Silva, Cláudia Maria de Oliveira Monteiro da [UNESP]; Rocha, Rosilene Fernandes da [UNESP] (Brazilian Archives of Biology and Technology, 2003)
O objetivo deste estudo foi avaliar os possíveis efeitos da tetraciclina administrada a ratas, no décimo dia de gestação, no desenvolvimento hepático e renal de seus filhotes. O fígado mostrou vacuolização, necrose, inflamação e dilatação sinusoidal mais evidente em recém-nascidos. Mitoses, aumento precoce da população de células de Kupffer e hipertrofia de hepatócitos com maior síntese de glicogênio estavam presentes no décimo e vigésimo dias de vida. O rim mostrou vacuolização tubular e necrose discretas, mais evidentes nos recém-nascidos, assim como sinais de regeneração tubular no décimo e vigésimo dias. Esses resultados sugeriram que os órgãos estudados sofreram alterações morfológicas transitórias durante o desenvolvimento, mas apresentaram sinais de regeneração ao longo dos primeiros dias de vida.

This study aimed on evaluating the possible effects of tetracycline administered to rats on the tenth day of pregnancy, on kidney and liver development of their offspring. The liver showed vacuolization, necrosis, inflammation and sinusoidal dilatations, more evident in the newborn. Mitosis, early increase of Kupffer cells population and hipertrophy of hepatocytes with greater synthesis of glycogen were present on the tenth and twentieth days of life. The kidney showed slight tubular vacuolizations and necrosis, more proeminent in the newborn, as well as signs of tubular regeneration on the tenth and twentieth days. These results suggested that the organs studied went through several transitory morphological changes during development but presented signs of regeneration along the first days of life.
Keywords: Pregnancy; Development; Tetracycline; Hepatotoxicity; Nephrotoxicity